Knowledge, Attitudes and Behaviors of the Adolescent Reproductive Health Triad: Case Study at the Vocational High School - Ahmad Yudi Satriyono; Hariyani Sulistyoningsih; Wuri Ratna Hidayani (Buletin Ilmu Kebidanan dan Keperawatan, 2022)
Puberty is experienced by every teenager which is characterized by the maturity of the reproductive organs thus triggering the sexual impulse. If the sexual drive in adolescents is not controlled then it is at risk to the Adolescent Reproductive Health Triad. The purpose of the study was to determine the relationship between knowledge and attitudes with the behavior of the Reproductive Health Triad at SMK Duta Pratama Indonesia Tasikmalaya City in 2021. This type of research is an analytical survey using a cross sectional design. The population and sample of this study are all students of SMK Duta Pratama Indonesia based on inclusion criteria. The instrument uses Gform and the data are analyzed univariately and bivariately. The results showed that the average knowledge score was 4.54, the average attitude score was 17.21, and the average behavior score was 5.51. There is no relationship between knowledge and behavior of the Adolescent Reproductive Health Triad p value = 0.135, and there is a relationship between attitudes and behavior of the Adolescent Reproductive Health Triad p value = 0.043. From the results of the study, it can be concluded that there is no relationship between knowledge and behavior of the Adolescent Reproductive Health Triad and there is a relationship between attitudes and behaviors of the Adolescent Reproductive Health Triad. It is hoped that the school can instill spiritual values and provide adolescent reproductive health education in preventing risky behaviors in students.